Customer Discrimination and Ethnic Team Composition - Ulf Rinne; Hendrik Sonnabend; Leonie Wolters (Institute of Labor Economics (IZA), 2023)
This paper examines the relationship between customer preferences and ethnic team composition in German professional soccer. Ethnic team composition is measured using facial recognition techniques, player names, and nationality. The study uses a difference-in-differences approach to show that after New Year's Eve 2015-16, third-division teams focusing on local and regional fans increased the share of native players by 6.4 to 12.2 percent compared to first- and second-division teams. Additionally, we find that in strongholds of the right-wing populist party AfD, a one-standard-deviation increase in the regional voting share for this party is associated with an increase in the share of native players by 3.1 to 3.6 percentage points. When examining the impacts of these changes in ethnic team composition on team productivity and economic success, we find that a higher share of (native) German players is neither associated with better performance outcomes nor higher attendance rates.
Keywords: J15; J44; J71; Z22; 330; ethnicity; soccer; labor market; discrimination; facial recognition